Introduction to modern physics - Richtmyer, F.K (McGraw-Hill Book Company, 1955)
Introduction to modern physics / Richtmyer, F.K. -- New York: McGraw-Hill Book Company, 1955 539 R498e5 5th ed No. of Copies : 1